(untitled) (Perner’s Contacts, 2015)
The vertical position of the car’s centre of gravity is one of the main parameters that influence vehicle handling and thus also the active traffic safety. The vehicle handling is nowadays frequently researched with the help of mathematical simulations, but for these it is necessary to provide correct values of the individual parameters of the vehicle. This study presents new approach to the measurement of the centre of gravity height with the help of a device which is primarily designated to measure the vehicle’s moments of inertia. This method utilizes the influence of the centre of gravity height on the value of the measured oscillation period of the designed device. The method is verified, first on the known parameters and then on the two vehicles.